On reduction of the (1+3)-dimensional inhomogeneous Monge-Ampère equation to the first-order partial differential equations - Fedorchuk, V. M.; Fedorchuk, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 512.813:517.957.6 We study a connection between the structural properties of two-dimensional nonconjugate subalgebras of the Lie algebra of the generalized Poincaré group P(1,4) and the results of symmetry reduction for the (1+3)-dimensional inhomogeneous Monge-Ampère equation. Some results concerning of the reduction of the equation under investigation to the first-order PDEs are presented.